(untitled) (American Journal of Islam and Society, 2003)
Reading this book is a lot like trying to eat undercooked meat – there is protein in there, but it is flavorless and tedious. You can chew and chew, but you just cannot bring yourself to swallow it. The author presents his case with an authoritative tone, stuffing each paragraph with names, dates, and historical data, but a closer look reveals the use of manipulative language that strings together half-truths and repeated insinuations with conclusions that do not directly relate to the given evidence. The “Acknowledgements” mention that the author has important friends in media and politics, yet his credentials (e.g., for whom he is working, or what his political motivations are) are not given. This is a serious weakness. Even more serious is his clear contempt for Islam, for he makes no genuine distinction between Muslims’ desire for self-rule based upon their belief system (often called “Islamism”) and terrorism. The CIA’s use of Muslim lives to advance American corporate interests is taken for granted, while Muslims are portrayed as untrustworthy imbeciles or ungrateful servants. Such mainstream and moderate organizations and intellectuals as Tablighi Jamaat, Jamaat Islami, Maududi of Pakistan, and Hassan al-Turabi of Sudan are given as examples of dangerous extremism. American terrorism against Iraq, Sudan, and Afghanistan, and its support of Israel, are unquestioned as being justified, noble, and necessary, while any attack on western interests or American lives is described with emotionally loaded terms. The only serious criticism of the United States is that it ever trusted Muslims as allies ...